تخليق ودراسة طيفية لبعض قواعد شف الجديدة وبعض معقداتها المحضرة بالطريقة الاعتيادية وطريقة الأشعة المايكرووية - خضير احمد عباس (University of Thi-Qar Journal of Science, 2014)
The present work include preparation of ligand (schiff base) derived from condensation reaction O-vanillin and with 1,3-diamino-2-propanol , was prepared by two different methods , the conventional heating and microwave methods , to give the following ligand: L: N,N-bis (2-hydroxy -3- methoxy benzalidene 1,3-diamino-2- propanol). As result the microwave assisted was remarkably successful with higher yield within less reaction time compared to conventional heating method. The ligand and its complexes have been characterized by elemental analysis , FTIR , UVVis , 1HNMR and Mass Spectra. The data show that the complexes have composition of ML type. The coordination behavior of the metal ions towards to the investigated Schiff bases takes place through –C=N and OH groups and the spectral analysis indicate octahedral geometry for all complexes.